Medication safety in a pandemic: A multicentre point prevalence study of QTc monitoring of hydroxychloroquine for COVID‐19. (6th May 2021) - Smoke, Steven M.; Leach, Henry; Leonida, Nicole; Raja, Karan; Shah, Monica; Patel, Vishal; Patel, Gargi; Daniel, Nicole M.; Gerges, Jessica; Patel, Akshar
Abstract: What is known and Objective: A pandemic can strain all aspects of the healthcare system, including the ability to monitor the safety of medication use. Reviewing the adequacy of medication safety practices during the COVID‐19 pandemic is critical to informing responses to future pandemics. The purpose of this study was to evaluate medication safety practices at a height of both COVID‐19 cases and hydroxychloroquine use. Methods: This was a multicentre observational point prevalence study. Adult inpatients receiving hydroxychloroquine for COVID‐19 between March 22 and 28, 2020 were included. The primary outcome was the percentage of patients receiving appropriate QTc monitoring. Secondary outcomes included QTc prolongation, early discontinuation of hydroxychloroquine and ventricular arrhythmias. Results and discussion: A total of 59% (167/284) of patients treated with hydroxychloroquine received appropriate QTc monitoring. QTc prolongation occurred in 25%. Hydroxychloroquine was prematurely discontinued in 1.4% of patients, all due to QTc prolongation. Ventricular arrhythmia occurred in 1.1%. What is new and Conclusion: Medication safety practices were suboptimal with regard to hydroxychloroquine monitoring at the height of the COVID‐19 pandemic. Preparation for future pandemics should devote considerable attention to medication safety. Abstract : This point prevalence study found that at the height of the COVID‐19 pandemic use of hydroxychloroquine was widespread despite being unproven. At the same time, medication safety practices in the form of QTc monitoring were suboptimal. Preparation for future pandemics should devote considerable attention to medication safety.